Effect of training about child neglect and abuse to teachers and its effect to awareness - İskender Gün; Adeviye Çopur; Elçin Balcı (BMC, 2022)
Abstract Background This study aimed to evaluate the effects of child neglect and abuse training on the knowledge and awareness of medical vocational schoolteachers in Turkey. Methods This study was conducted based on data taken from a sample of teachers from Kayseri, Turkey, between October 2016 and April 2017. Teachers who agreed to participate in the study received training pertaining to child neglect and abuse. Data were collected through a survey form and the Scale for Identifying the Symptoms and Risks of Child Abuse and Neglect. Data were analyzed using SPSS V.20.0 software. For statistical analyses, Student's t test, analysis of variance and McNemar tests were conducted, with a value of p <  0.05 being considered statistically significant. Results Of teachers in the sample, 63.7% were female, and 80.5% were married. Teachers' mean age was 40.5 ± 9.9 years. Among teachers, 87.4% reported that the training was sufficient. Teachers' level of knowledge concerning neglect and abuse and the percentage of teachers who reported that they would report such situations to the authorities when faced with such a case increased after training. Female teachers' scores on the neglect and abuse scale increased among teachers without children and those who found the training to be sufficient. Conclusions The knowledge level of teachers in the study group was found to be increased compared to their knowledge level prior to training. The subject of child neglect and abuse should be further discussed in the context of teachers' formal training.